THE RISE OF CHIVALRIC ROMANCE IN MEDIEVAL ENGLISH LITERATURE (Ustozlar uchun, 2025)
One of the most significant literary forms of the Middle Ages was the chivalric romance, which shaped medieval Europe's cultural imagination and established narrative templates that persisted into later English literature.  The evolution of chivalric romance in medieval English literature is examined in this article, with particular attention paid to its key works, cultural purposes, thematic components, and historical foundations.  It demonstrates how literary inventiveness and the principles of chivalry courage, loyalty, civility, and courtly love - intersected to create classic stories like Sir Gawain and the Green Knight, Malory's Le Morte d'Arthur, and the Anglo-Norman romances.